Evaluation of stryphnodendron sp. release using natural rubber latex membrane as carrier - Romeira, Karoline Mansano [UNESP]; Drago, Bruno C.; Murbach, Heitor Dias [UNESP]; Aielo, Patricia Businaro [UNESP]; Silva, Regildo Márcio Gonçalves da [UNESP]; Brunello, Carlos A.; Herculano, Rondinelli Donizetti [UNESP] (Science Alert, 2012)
Natural rubber latex from Hevea brasiliensis has interesting characteristics related to this work such as: it is easy to manipulate, low cost, can stimulate the natural angiogenesis, is a biocompatible material and presents high mechanical resistance. The aim of this study was to develop a novel sustained delivery system for Stryphnodendron sp. based on Natural Rubber Latex (NRL) membranes and to study the Stryphnodendron sp. delivery system behavior. Stryphnodendron sp., commonly known as barbatimao is extensively used in folk medicine for the treatment of diarrhoea, gynaecological problems and for healing wounds. The stem bark of this species is mentioned in the Brazilian Pharmacopeia with a content of at least 20% of tannins. Previous studies showed significant cicatrizant properties, anti-inflammatory activity and gastric anti-ulcerogenic effects for the stem bark crude extract. One possible way to accelerate the tissue repair process, it was incorporated the Stryphnodendron sp. extract in NRL membranes. Stryphnodendron sp extract was incorporated into the NRL, by mixing it in solution for in vitro protein delivery experiments. Results show that the NRL membrane can release Stryphnodendron sp. for up to 49.89% of its Stryphnodendron sp. content for up 400 h. The kinetics of the extract release could be fitted with double exponential function, with two characteristic times of 0.78 and 133.22 h. In this study, we demonstrated that the induced angiogenesis provided by NRL membranes combined with a controlled release of extract is relevant for biomedical applications.
Keywords: Latex membrane; Drug Delivery System; barbatimao; Stryphnodendron sp